1991
DOI: 10.1016/s0003-3472(05)80842-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of dyadic conflict in male green swordtail fish, Xiphophorus helleri: Effects of body size and prior dominance

Abstract: Abstract. The relative contribution of prior experience and of size asymmetries to the determination of dyadic dominance between unfamiliar individuals was examined using pairs of green swordtail fish, Xiphophorus helleri. Three experiments were conducted to assess the extent to which superiority in size could override potential handicaps resulting from prior experience. These results indicated that prior experience accounted for dyadic dominance when the size advantage of a previously subordinate over a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 14 publications
3
68
2
Order By: Relevance
“…Ribowski & Franck 1993a), and has been studied quite extensively (e.g. Franck & Ribowski 1987Beaugrand et al 1991;Ribowski & Franck 1993b). In addition, swordtails form strict linear dominance hierarchies both in the laboratory and in the ® eld, a social environment that should be conducive to networking effects (Beaugrand et al 1984;Franck & Ribowski 1993;Franck et al 1998;Earley & Dugatkin 2002).…”
Section: Procmentioning
confidence: 99%
“…Ribowski & Franck 1993a), and has been studied quite extensively (e.g. Franck & Ribowski 1987Beaugrand et al 1991;Ribowski & Franck 1993b). In addition, swordtails form strict linear dominance hierarchies both in the laboratory and in the ® eld, a social environment that should be conducive to networking effects (Beaugrand et al 1984;Franck & Ribowski 1993;Franck et al 1998;Earley & Dugatkin 2002).…”
Section: Procmentioning
confidence: 99%
“…Knowledge of some animals' physical attributes or past dominance history enables the human observer to predict the direction of the dominance relation when those animals are put together (Beaugrand et al, 1991. Behavioural acts evident at the onset of an encounter can also help to predict, with a high success rate, which subject will dominate.…”
Section: Discussionmentioning
confidence: 99%
“…In the Martin et al (1997) study, weight asymmetries were opposed to recent experience asymmetries in the hope of seeing one cancelling or overcoming the other as Beaugrand et al (1991Beaugrand et al ( , 1996 had obtained in green swordtail fish. Martin et al (1997) did not find that weight significantly increased chances of victory, contradicting the conclusions drawn by Murchison (1935) and by Guhl and Allee (1944), who reported that heavier subjects were more likely to adopt aggressive behaviour and to hold a higher position in the social hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…individuals that are familiar with, and have invested in, a territory or environment] have a greater likelihood to dominate intruders or newcomers [i.e. individuals that are unfamiliar with a territory or environment upon meeting the resident] than vice versa (Braddock, 1949;Thinès & Heuts, 1968;Heuts, 1979;Beaugrand et al, 1991Beaugrand et al, , 1996Heuts & Nijman, 1998). It stems from a pay-off asymmetry between residents and intruders.…”
Section: Introductionmentioning
confidence: 99%